2007
DOI: 10.1111/j.1467-6494.2007.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

The Why's the Limit: Curtailing Self‐Enhancement With Explanatory Introspection

Abstract: Self-enhancement is linked to psychological gains (e.g., subjective well-being, persistence in adversity), but also to intrapersonal and interpersonal costs (e.g., excessive risktaking, antisocial behavior). Thus, constraints on self-enhancement may sometimes afford intrapersonal and interpersonal advantages. We tested whether explanatory introspection (i.e., generating reasons for why one might or might not possess personality traits) constitutes one such constraint. Experiment 1 demonstrated that explanatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 104 publications
(142 reference statements)
3
32
0
1
Order By: Relevance
“…By instructing employees to give examples of their behavior on the basis of the feedback and to give them some time to step back and reflect on their performance, employees may be more inclined to see value in the feedback provided and react more positively to it. This expectation is undergirded by previous findings that increased introspection leads to more accurate and less inflated self-views (Sedikides, Hortin, & Gregg, 2007). In turn, we expect these favorable feedback reactions to be related to performance improvement after feedback, as suggested in previous research (Kinicki et al, 2004).…”
Section: Hypothesis 1: Performance Will Increase More In a Group Who supporting
confidence: 65%
“…By instructing employees to give examples of their behavior on the basis of the feedback and to give them some time to step back and reflect on their performance, employees may be more inclined to see value in the feedback provided and react more positively to it. This expectation is undergirded by previous findings that increased introspection leads to more accurate and less inflated self-views (Sedikides, Hortin, & Gregg, 2007). In turn, we expect these favorable feedback reactions to be related to performance improvement after feedback, as suggested in previous research (Kinicki et al, 2004).…”
Section: Hypothesis 1: Performance Will Increase More In a Group Who supporting
confidence: 65%
“…In keeping with this suggestion, Sedikides, Horton, and Gregg (2007) reported that participants who reflected on why they might or might not possess negative central traits (e.g., untrustworthy, unkind, unfriendly) rated themselves more unfavorably on those traits than control participants did.…”
Section: Mnemic Neglect Model 29mentioning
confidence: 69%
“…Because self-analysis is frequently a complex and obscure task, however (Sedikides, Horton, & Gregg, 2007), dramatic processes such as repression and denial rarely need to be invoked. To take a mundane example, analyzing one's traits and abilities requires assessing how one fares in the general distribution of these performance over time and were exposed to the same social comparison information.…”
Section: Self-enhancement and Self-protection 28mentioning
confidence: 99%